Return on Assets in the Automotive Sub Sector Company: working capital turnover, company size, current ratio, debt to equity ratio - Adityo Alif Rahman Kusumo; Kumba Digdowiseiso (LPMP Imperium, 2023)
The purpose of this study was to determine the factors that influence return on assets (ROA) in the automotive and component sub-sector companies. There are four factors tested, namely, working capital turnover (WCTO), company size, current ratio (CR), and debt to equity ratio (DER). The automotive sub-sector companies that make up the population of this study are companies listed on the Indonesia Stock Exchange (IDX) for the 2011-2020 period. Sampling using purposive sampling technique, obtained from a population of 13 companies into nine companies as a sample. Proof of the results was carried out by means of panel data regression analysis through STATA 16. Data processing showed that the results were only CR which did not significantly affect ROA. While the WCTO is positively significant, firm size and DER have a significant negative effect on ROA. Suggestion, due to the variation in results, future researchers need to do research in a longer term.